The LysR family transcriptional regulator ORF-L16 regulates spinosad biosynthesis in Saccharopolyspora spinosa - Xin Mu; Ru Lei; Shuqing Yan; Zixin Deng; Ran Liu; Tiangang Liu (Synthetic and Systems Biotechnology)
Spinosad, a potent broad-spectrum bioinsecticide produced by Saccharopolyspora spinosa, has significant market potential. Despite its effectiveness, the regulatory mechanisms of spinosad biosynthesis remain unclear. Our investigation identified the crucial role of the LysR family transcriptional regulator ORF-L16, located upstream of spinosad biosynthetic genes, in spinosad biosynthesis. Through reverse transcription PCR (RT-PCR) and 5′-rapid amplification of cDNA ends (5′-Race), we unveiled that the spinosad biosynthetic gene cluster (BGC) contains six transcription units and seven promoters. Electrophoretic mobility shift assays (EMSAs) demonstrated that ORF-L16 bound to seven promoters within the spinosad BGC, indicating its involvement in regulating spinosad biosynthesis. Notably, deletion of ORF-L16 led to a drastic reduction in spinosad production from 1818.73 mg/L to 1.69 mg/L, accompanied by decreased transcription levels of spinosad biosynthetic genes, confirming its positive regulatory function. Additionally, isothermal titration calorimetry (ITC) and EMSA confirmed that spinosyn A, the main product of the spinosad BGC, served as an effector of ORF-L16. Specifically, it decreased the binding affinity between ORF-L16 and spinosad BGC promoters, thus exerting negative feedback regulation on spinosad biosynthesis. This research enhances our comprehension of spinosad biosynthesis regulation and lays the groundwork for future investigations on transcriptional regulators in S. spinosa.